(untitled) (Window of Public Health Journal, 2025)
Fatigue is a combination of mental and physical function decline that reduces work enthusiasm, decreasing work effectiveness and efficiency. This study aims to determine the factors associated with work fatigue in workers at PT. Maruki International Indonesia in 2023. To achieve this, we conducted a quantitative study with a cross-sectional design. We used a total sampling technique, surveying all 64 workers in factory 1. Data were obtained using a questionnaire to measure various factors related to work fatigue. We then used univariate and bivariate analysis, including the chi-square test, to analyze the data. The results showed a relationship between age and work fatigue (p-value = 0.000 <0.05). There was a relationship between workload and work fatigue (p-value = 0.000 <0.05). There was no relationship between length of service and work fatigue. There was no relationship between work period and work fatigue. There was no relationship between nutritional status and work fatigue (p-value = 0.595 >0.05). From the results of this study, the researcher suggests that companies should provide more attention to older workers, providing sufficient rest time and reducing the workload given to minimize work fatigue, and also for workers to maintain normal nutritional status.